The Role and Importance of the Spiritual Heritage of Sufi Allahyarin the Upbringing of a Harmonious Person - Zarina Akhtamovna, Khimmatova (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the role of the spiritual heritage of the great scientist and thinker Sufi Allahyar, who was considered one of the poets who worked in two languages in Uzbek literature, the great representative of the Naqshbandiyan sect, who took an important place in the history of Uzbek Enlightenment, who lived in Central Asia in the second half of the XVII and the beginning of the XVIII. Sufi Allahyar created four major works in the philosophical-moral-pedagogical and literary-didactic direction. They are "Maslakul – muttaqin" and "Muradul – orifin" in Persian, "Sabot ul – ojizin" in Turkish-Uzbek, and "Maslakul – mutiyn" in Arabic. In the article, the ideas of the scientists "Maslakul-mutaqqin, Sabot ul-ojizin," and several poetic samples were studied; socio-philosophical views and views on the upbringing of a perfect person and the importance of his role in the upbringing of the individual in today's period were revealed.